Use of acridine orange to visually improve the loop-mediated isothermal amplification for detection of infectious spleen and kidney necrosis virus - Subramaniam, Kuttichantran; Mohamed Din, Mohamed Shariff; Omar, Abdul Rahman; Bejo, Mohd Hair; Ong, Bee Lee (Japanese Society of Fish Pathology, 2014)
The advancement in nucleic acid amplification has improved the diagnostic methods for many diseases. In the current study, an improved technique for the detection of infectious spleen and kidney necrosis virus (ISKNV) based on loop-mediated isothermal amplification (LAMP) is described. The addition of acridine orange at the end of the reaction causes distinct color change which can be recognized by the naked eye. In addition, a new set of primers was designed based on the ISKNV major capsid protein (MCP) gene sequences. The primers are highly specific for ISKNV and there was no cross amplification with red sea bream iridovirus (RSIV), white spot syndrome virus (WSSV), Aeromonas hydrophila or Vibrio parahaemolyticus. The detection limit of LAMP assay was 1.4 × 104 copies of the virus DNA and the optimum temperature and time for assay was 65°C and 60 min respectively, and this protocol could successfully detect the virus from asymptomatically infected fish. This improved LAMP assay is a simple and inexpensive diagnostic tool for the detection of ISKNV without the need of specialized equipment.